POTENSI PAJAK KENDARAAN BERMOTOR (PKB) DI DILI TIMOR LEST - , Ivonio de Oliveira Marcal, Dra. Sri Handaru Yuliati M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to calculate the potential of the Motor Vehicle Tax in Dili East Timor in 2012. The study also aims to determine the classification of Motor Vehicle Tax in Dili Timor Leste in 2007-2011 in four categories: (1) prime, (2) potential, (3) developing and (4) backward. The data used to support this research is secondary data. Data obtained include the realization of the data revenues and expenditures, motor vehicle tax and the number of vehicles in Dili, Timor Leste. The analysis tools are potential analysis and classification of motor vehicle tax and linear trend analysis for the projected number of motor vehicles in 2012. The analysis showed that the potential of the Motor Vehicle Tax in Dili Timor Leste is continuously increased from 2007 to 2011. However, the growth potential of motor vehicle tax in Dili Timor Leste has fluctuated. Classification by type of motor vehicle taxes: 1. Motor vehicle registration tax in 2008 in a state of potential and in 2009 was on the classification of prime and in 2010-2011 the idea of potential conditions, 2. Tax Administration in 2008 on the classification developed, in 2009 on the classification of retarded, the classification developed in 2010 and in 2011 on the classification of prime